Sudden, Severe Mitral Insufficiency - Auger, Pierre (1967)
Five male patients with sudden, severe mitral insufficiency due solely to ruptured chordae tendineae or papillary muscle had an abrupt onset of symptoms of left and right heart failure and the sudden appearance of a harsh, widely propagated apical pansystolic murmur. None had a history of rheumatic fever. All were in sinus rhythm and had but mild left atrial and ventricular enlargement. Giant left atrial “v” waves were characteristic and exceeded pulmonary artery pressure in two instances. In contrast, when ruptured chordae tendineae were superimposed on chronic rheumatic mitral insufficiency, females predominated and there was a long history of disability. Atrial fibrillation, less elevation of left atrial pressure, and marked left atrial and ventricular enlargement were characteristic. These latter patients closely resembled patients with chronic rheumatic mitral insufficiency alone. It is concluded that the syndrome of sudden, severe mitral insufficiency develops if ruptured chordae tendineae occur on a previously normal or insignificantly diseased mitral valve. If ruptured chordae tendineae are superimposed on chronic rheumatic mitral insufficiency, the syndrome resembles that seen in the latter alone.